ANALISIS EMPATI SISWA KELAS VII ( TUJUH ) SMP NEGERI 3 PUJUD - Umari, Tri Umari Tri; Arlizon, Raja Arlizon Raja; ', Awaluddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack This study entitled "ANALYSIS OF EMPATHY CLASS VII (SEVEN) SMP STATE 3 Pujud". This research aims to increase the sense of empathy seventh grade students of SMP Negeri 3. phenomenon found in SMP Negeri 3 Pujud this is lack of compassion for the suffering of friends, students often offend and hurt his feelings, absence of harmony and harmony in the mix, number of students in speak using words not polite, less concerned with the shortage of friends, students mocked and insulted friends, both in terms of economic and physical. From the above phenomena can be formulated problem is: How can a general idea of empathy level students in class VII (Seven) SMP Negeri 3 Pujud?, How empathy level overview of students by gender of students in class VII (Seven) SMP Negeri 3 Pujud?, How overview empathy students per item on class VII (Seven) SMP Negeri 3 Pujud?. from the formulation of the problem can be seen that the purpose of this study is: To determine the general picture of empathy level students in class VII (Seven) SMP Negeri 3 Pujud, To know the description of empathy level students by gender for students in grade VII (Seven) SMP Negeri 3 Pujud, How empathetic depiction of students per item on class VII (Seven) SMP Negeri 3 Pujud. The method used in this research is to use the comparative method, and the data processed in this study is data about student emoati men with women in SMP Negeri 3 Pujud. And the population in this study were all students of class VII (Seven) SMP Negeri 3 Pujud which amounted to 2 classes. each class consists of 28 students. Data collection tool was a questionnaire, which is about empathy questionnaire consisting of 20 questions. Keywords:EmpathyStudentsMaleandFemaleStudents